FORMATION AND DEVELOPMENT OF MANAGEMENT - Abdukarimova Shakhnoza (Scholar Express Journals, 2023)
The article highlights the problems of modern management and the trend of its development. The definition and characteristics of the concept of "management" are given, its evolution from ancient times to the present is briefly touched upon. Attention is paid to the emerging trends in the development of science and practice of management, as well as objective factors influencing the designated process.
Keywords: modern management; management development factors; management development trends